Preconcepts in Physics. Report to the John Abbott College Research and Development Committee - Dickie, L. O.; John Abbott Coll., Sainte Anne de Bellevue (Quebec). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
This study was conducted to examine the basic conceptual knowledge and understanding of physics possessed by students enrolled in introductory physics, mechanics and waves and optics courses at John Abbott College (JAC). The study used a 36-item multiple-choice test of physics preconcepts developed by Halloun and Hestenes. The Halloun and Hestenes test was administered to 510 JAC students and to 57 high school students at a neighboring feeder high school, and results were compared with Halloun and Hestenes' results of an administration of the test to high school, university, and college students in Arizona. Results were also compared with those of Desautels, who used an 11-item test to assess francophone two-year college students' preconcepts and understanding of uniformly accelerated motion. Study findings included the following: (1) the conceptual knowledge of the Quebec high school students was consistent with that of the Arizona high school students; (2) conventional instruction did little to improve JAC students' and Arizona college students' understanding of mechanics concepts; (3) the mechanics scheme held by most JAC students was comparable to that held by students in other countries; (4) in Quebec, language of instruction did not affect the development of students' understanding of the conceptual framework of mechanics; and (5) Halloun and Hestenes' test could not serve by itself as a placement test for the mechanics course at JAC. (WJT)
Educational level discussed: Two Year Colleges.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Colleges; Comparative Analysis; Foreign Countries; French Canadians; High School Students; Knowledge Level; Language of Instruction; Mechanics (Physics); Physics; Science Instruction; Science Tests; Student Evaluation; Two Year College Students; Two Year Colleges; Reports, Research